COVID-19, normative attitudes and pluralistic ignorance in employer-employee relationships - Martin Abraham; Matthias Collischon; Veronika Grimm; Frauke Kreuter; Klaus Moser; Cornelia Niessen; Claus Schnabel; Gesine Stephan; Mark Trappmann; Tobias Wolbring (Journal for Labour Market Research, 2022)
Employment relationships are embedded in a network of social norms that provide an implicit framework for desired behaviour, especially if contractual solutions are weak. The COVID-19 pandemic has brought about major changes that have led to situations, such as the scope of short-time work or home-based work in a firm. Against this backdrop, our study addresses three questions: first, are there social norms dealing with these changes; second, are there differences in attitudes between employees and supervisors (misalignment); and third, are there differences between respondents' average attitudes and the attitudes expected to exist in the population (pluralistic ignorance). We find that for the assignment of short-time work and of work at home, there are shared normative attitudes with only small differences between supervisors and nonsupervisors. Moreover, there is evidence for pluralistic ignorance; asked for the perceived opinion of others, respondents over- or underestimated the consensus in the (survey) population. Such pluralistic ignorance can contribute to the upholding of a norm even if individuals do not support the norm, with potentially far-reaching consequences for the quality of the employment relationship and the functioning of the organization. Our results show that, especially in times of change, social norms should be considered for the analysis of labour markets.
Keywords: D91; J50; J81; 330; Employment relationship; Social norms; Pluralistic ignorance; Short-time work; Working from home